Multilingualism and Polyphony: Post-modernism Features in "Possible Night" (Shab-e Momken) Novel - Nooshin Ostadmohamadi; Maryam Hoseini (مطالعات زبانی و بلاغی)
Iranian fiction atmosphere, in the past two decades, is strongly under the influence of Schools and literary movements, such as postmodernism. “Possible night” is Mohammad Hassan Shahsavari’s second novel that with seven years away, toward his first work "Pagard" published and was attracted by most of its readers. This novel consists of five chapters. One of the features of this work is rejecting and changing many events and incidents from previous seasons by changing the narrator in the next chapter.  The method of this article is descriptive – analytical. Authors will prove this is a postmodern novel with components such as “metafiction”, “uncertainity”, “multiple ending”, “short circuit”, and “intertextuality”. Intertextual relationships in the novel include: some poems of Hafiz, Saadi, Ferdowsi. But one of the main intertextual relationship in this novel is related to “auto stop play” that is part of Milan Kundera’s “Laughable Loves” and Shahsavari in parts of his work deliberately benefited from that book.